(untitled) (World Bulletin of Social Sciences, 2024)
Primary education plays a key role in shaping the academic, social and cognitive development of young students. This scientific article talks about the importance of introducing best practices in improving the effectiveness of primary education. By examining key strategies such as curriculum design, teacher training, technology integration, and community engagement, this article aims to provide insight into how these practices can be used to optimize the early learning experience for students